Real-life treatment patterns and time to next treatment among patients with ovarian cancer in the pre-PARP inhibitor era: the OCRWE-Finland Study - Lahelma, Mari; Rauhamaa, Heini; Isomeri, Outi; Idänpään-Heikkilä, Juhana; Käkelä, Sari; Roebuck, Nichola; Mascialino, Barbara; Hietanen, Sakari; Loukovaara, Mikko; Auranen, Annika (Medical Journal Sweden AB, 2025)
Background: As the treatment landscape for advanced ovarian cancer (OC) evolves, it is important to understand patient outcomes in real-world clinical practice. OCRWE-Finland was an observational cohort study investigating OC outcomes, including treatment patterns, time to next treatment 1 (TTNT1), overall survival and healthcare resource utilisation, in Finland during the pre-PARPi era.
Materials and methods: Patients included in OCRWE-Finland were diagnosed with OC between 2014 and 2019. Here, we report treatment patterns and TTNT1 outcomes (as a surrogate for progression-free survival) for patients in the high-grade serous ovarian carcinoma (HGSOC) cohort.
Results: In OCRWE-Finland, there were 867 patients with HGSOC. Of the 811 patients who received first-line treatment, the most common regimen was surgery and adjuvant chemotherapy (53%), and 227 patients also received first-line bevacizumab. Median TTNT1 among 623 patients with stage III/IV disease was 19 months (95% confidence interval, 18-21 months), with no difference between patients with stage III or IV disease (p = 0.24). The presence versus absence of visible residual disease post-debulking surgery was associated with shorterTTNT1 among patients with stage III tumours (p = 0.031) but showed no impact for stage IV tumours (p = 0.55). First-line versus no first-line bevacizumab was associated with shorter TTNT1 among stages I-IV (p < 0.0001) but did not affect patients with stage III/IV tumours (p = 0.45).
Interpretation: In the pre-PARPi era, prognosis for advanced OC was poor, particularly for patients with stage III tumours and visible residual disease or stage IV tumours regardless of the presence of residual disease. The increasing use of PARPis will hopefully help address the need for effective treatments in advanced OC.